What are the main determinants of smoking in African/Middle East college students? - Ravara, Sofia Belo; Adam, Bukhari Abubakar; Pirincci, Edibe (European Respiratory Soc Journals Ltd, 2021)
[Abstract Not Available]
European-Respiratory-Society (ERS) International Congress -- SEP 26-30, 2021 -- Thessaloniki, GREECE
Keywords: Education; Smoking; Health policy